Factors influencing fast food restaurants advertisements effectiveness : an exploratory study of Malaysian customers - Almas Bte Mohd Asri
The purpose of this paper is to explore customer's views on fast food restaurants advertising- print production, commercial advertising and internet advertising. There are two factors which also can impact on fast food restaurants advertising- likeability and entertainments. Data were collected by using a survey method in Klang Valley areas, Malaysia. 300 questionnaires were distributed and recorded with a response rate of 85 per cent. In the findings, customers are more attracted to advertisements of fast food restaurants such as print production, commercial advertising, and internet advertising of fast foods, likeability and entertainment. These factors have significant linked to the effectiveness of advertising. The findings suggested some significant of implications which will help advertisers to create better fast food restaurant advertisements. For example, managers can change slogans based on current situations which will help them to prepare on create suitable advertising for customer. In addition, manager also can use to create specific massage to update information or change format in promotional campaign.